Meandered CPW‐fed hexagonal split‐ring resonator monopole antenna for 5.8 GHz RF‐ID applications. Issue 3 (March 2015) - Pandeeswari, R.; Raghavan, S.
ABSTRACT The design of a compact monopole antenna for 5.8 GHz RFID application is presented. Hexagonal split ring resonator is used as radiating element and is fed with meandered CPW feed line. Meandered CPW feed line is used to improve the impedance matching of the antenna. The antenna prototype is fabricated and tested. The proposed antenna is fabricated on FR4 substrate and occupies a small size of 13 × 19.8 × 0.8 mm3. The measured results of the proposed antenna show that the impedance bandwidth is from 5.4 to 6.0 GHz. Good omnidirectional pattern obtained in H‐plane and bidirectional pattern obtained in E‐plane. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:681–684, 2015